A robotic manipulator trajectory monitoring system in virtual environment - Hatam Dalef, Huda (2018)
The user interface or commonly known as human–computer interaction (HCI) has become the focus of most researches as the usage of computers increases in nearly all manufacturing machines. The design parameters of HCI include hardware and software related parameters. Virtual Environment (VE) can be employed to interpret these interactions; however it is challenging to integrate VE-assisted simulation tools because the hazard of touching the machine and the difficulty of monitoring are among the most prominent problems in intelligent industries. Many accidents have been associated with robot manipulator operations, where the total number of fatalities in the United States was 4,585 and over 1,300 workers were injured in 2013, because of hardware and software complexity or the insufficient knowledge and skills of technicians in operating and monitoring the equipment. The accurate control of motion axes is a fundamental concern in intelligent industries, in which an exact end-effector trajectory is required at the correct time. It is also essential for efficient system operation and to predict the position and time error of the trajectory. Therefore, there is a need for a solution that can provide convenient and intuitive robot manipulator control with user’s location independence, easy adjustment and simultaneous monitoring of robot manipulator motion tasks. The main objective of this research is to develop a robotic manipulator trajectory monitoring system in VE. Therefore, the first objective is to enhance monitoring trajectory system of robot manipulator using wireless control system. Additionally, to describe the trajectory a mathematical model and parameter optimization based on VE data was derived. This work adopts a robot manipulator as a scale down of the actual industrial machine. The Zigbee-based wireless communication system consists of only a pair of XBee S1 Pro. MATLAB graphical user interface GUI-based environment involving the 3- D animation of the actual structure is presented to demonstrate real-time moving of the end-effector trajectory. An integrated VE control and monitoring trajectory (VECMT) was built by matching the digital information with the user’s environment, and a mathematical model was derived for the 3D structural mechanism to verify the VECMT system. In order to model the system hardware which was used to predict robot manipulator trajectory and enhance the overall monitoring system, Nonlinear Least Squares method was used as a measurementbased parameter optimization procedure. Therefore, this work presents several novel contributions to improve the trajectory state robot manipulator in VE. Firstly, the main achievement of this work is low power consumption for a wireless data network for 3D position monitoring, the proposed approach is efficient in terms of user cost level contribution because it adopts the concept of signal matching in the software configuration of components and a suitable selection of components dispenses of additional microcontrollers which ultimately achieves economic cost reduction. Secondly, the user perceives an integrated computer-based work environment and allows the user to easily merge the real world with a computer based environment in a high accuracy of 98.53% for elbow’s joint and 97.5% for the base’s joint. The estimation of the parameter simulation has been verified by comparing the target data with response data that shows a very good convergence (97.87% for elbow and 98.69% for base).